Mind and media the effects of television, video games, and computers - Greenfield, Patricia Marks (New York Psychology Press, 2014)
"Patricia M. Greenfield was one of the first psychologists to present new research on how various media can be used to promote social growth and thinking skills. In this now classic, she argues that each medium can make a contribution to development, that each has strengths and weaknesses, and that the ideal childhood environment includes a multimedia approach to learning. In the Introduction to the Classic Edition, Greenfield shows how the original edition set themes that have extended into contemporary research on media and child development, and includes an explanation of how the new media landscape has changed her own research and thinking"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Mass media and children; Television and children; Video games; Child development